THE INFLUENCE OF REGIONAL GENUINE INCOME, BALANCED FUNDS AND BUDGET RETURN CALCULATIONS (SILPA) ON CAPITAL EXPENDITURES IN INDONESIAN PROVINCE - Marzuki; Halida Bahri; Chairil Akhyar; Hairani Putri (PT. Radja Intercontinental Publishing, 2023)
This study aims to analyze the effect of regional original income, balancing funds, and excess budget calculations on capital expenditure in provinces throughout Indonesia. The population in this study totaled 34 provinces. The samples used in this study amounted to 34 provinces. The type of research used is quantitative.Quantitative research is a study that emphasizes the analysis of numerical data (numbers) that are processed using certain statistical methods. The data collection technique used in this study was a documentation technique and analyzed using panel data regression and processed using the Eviews9 application. The results of the study found that the variable regional original income (PAD) had a positive and significant effect on capital expenditure, while balancing funds (DP) and remaining budget calculations (SiLPA) had a negative and insignificant effect on capital expenditure.